Genomic analyses reveal a lack of widespread strong selection in indigenous chickens - Zilong Wen; Xinyu Cai; Zexuan Liu; Lizhi Tan; Yuan Kong; Yuzhan Wang; Yiqiang Zhao (Poultry Science)
The study of domestication has been revolutionized with the advent of molecular genetics. Chickens, with their clear domestication history, emerge as an excellent model for study into the paths of evolution in domestication and improvement. Here we used genomic data from wild, indigenous, and commercial chickens to better understand how genetic drift and selection translate into their differentiations. Our investigation into the patterns of allelic change and divergence reveals a polygenic architecture governing genetic differentiation during domestication and improvement. We uncover distinctive population-specific differentiations in terms of genes and functions among wild, indigenous, and commercial chickens. Using Runs Of Homozygosity (ROH) based mixed model approach developed in this study, we identified only directional selection signatures occurring in wild and commercial chickens. Notably, our findings suggest that indigenous chickens serve as reservoirs of genetic diversity, necessary for rapid adaptation to new environments or subsequent modern breeding. This work provides unprecedented insights into the chicken domestication and improvement, and it illuminates our understanding of the domestication of other animal species.